The importance of achieving security culture in enhancing the status of companies: the Egyptian airlines as a case study - Acharbini, Mohamed (Finance and Business Economies Review, 2019)
The study aimed to identify the importance of security culture in enhancing the stability of companies, in addition to identifying the obstacles facing the enhancement of this culture among employees of the Egyptian airlines. The study found that spreading the security culture among the employees of the airlines is of great importance. It will help in preparing employees capable of facing the security threats and improving the mental image of the security situation of the Egyptian airlines. Among the most important obstacles was the lack of funds allocated to spread security culture and training in various security situations.